IMPLEMENTASI KONSEP ARSITEKTUR EKOLOGI PADA RANCANG BANGUN RUMAH MINIMALIS - Sidik Sidik; Daniel Fauzi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2016)
The need for housing for everyone is increasing, making the property developers need various innovations in the provision of housing facilities. Additionally, utilization of natural resources is no longer counted how much impact it will have, add to the damage of this nature. In this study, the authors analyzed the problem of materials, technology, structure, lighting, building orientation, for building both traditional and modern minimalist as well as design application that can be applied in developing ecological architecture and environmentally friendly in terms of the health of its inhabitants. In order to look more real and interesting, the authors make a minimalist home architecture design ecologically oriented interactive animations. The method used in this paper is a qualitative method with a descriptive approach. The results of this study indicate that the ecological building, especially in terms of the science of architecture. In terms of lighting and choosing the material does not cause the nature, the location of the building facing south is the most excellent in the ability to withstand heat.